Polarization around issues related to religion and religiosity on the example of the new media dispute over open churches during easter in 2021 - Christian Körber, Andy (Research on social problems in (pre-)pandemic reality, 2023)
In the sociology of religion, the Internet is mainly treated as a new place to participate in religious practices or to obtain religious knowledge. However, it is not studied as a kind of public sphere where the meaning and forms of religion and the aforementioned practices are debated. Therefore, the role of new media in defining the direction of contemporary religious changes remains poorly recognized. The subject of the article is an analysis of how the Internet discourse reflects social divisions in the area of religion and religiosity. Using the so-called framing analysis the article focuses on the online dispute over open churches during Easter in 2021 and reconstructs 12 media frames on the basis of 162 texts from popular Polish websites. It has been noted that most of them are characterized either by the criticism of the institution of the Roman Catholic Church or its defense, which may be associated with the polarization of the discourse on religion and religiosity in Poland. On the other hand, Internet texts rarely provide answers to the question of how to reconcile the need for personal participation in important religious holidays with concern for health in the next peak of the pandemic.